The sociodemographic patterning of drinking and binge drinking in Estonia, Latvia, Lithuania and Finland, 1994–2002 - Petkeviciene Janina (BMC Public Health, 2007)
Abstract Background Despite the relatively low recorded alcohol consumption level, the Baltic countries (Estonia, Latvia and Lithuania) and neighbouring Finland suffer from similar harmful consequences related to the use of alcoholic beverages, including socio-economic inequalities in alcohol related mortality. Comparative evidence is needed to understand harmful drinking patterns and to implement preventive alcohol policies also in the Baltic countries. This study compared heavy and binge drinking by sex, age, education, urbanisation and marital status in the Baltic countries and Finland. Methods The data were nationally representative postal surveys conducted in Estonia (n = 6271), Latvia (n = 6106), Lithuania (n = 7966) and Finland (n = 15764) during 1994–2002. The criterion for heavy drinking was at least 15 portions weekly among men, and at least five among women, and for binge drinking at least six portions per one occasion. Results Heavy drinking was more common among younger participants in all countries, and in Latvia among the less-educated. Among Finnish men, and among women from all countries except Latvia, the better-educated were more often heavy drinkers. In Latvia and Finland, urban men, and in all countries, urban women, were more often heavy drinkers. Heavy drinking was more common among non-married Lithuanian and Finnish men, and Finnish women. Binge drinking was more common among less-educated Estonian and Latvian men, and among younger and less-educated women in all countries. Conclusion Our results support the continued power of traditional drinking habits in the North Eastern part of Europe. In the future the target groups for prevention of excessive drinking should also include young and less-educated women in all four countries studied.